2015
DOI: 10.1038/srep09149
|View full text |Cite
|
Sign up to set email alerts
|

The multikinase inhibitor Sorafenib enhances glycolysis and synergizes with glycolysis blockade for cancer cell killing

Abstract: Although the only effective drug against primary hepatocarcinoma, the multikinase inhibitor Sorafenib (SFB) usually fails to eradicate liver cancer. Since SFB targets mitochondria, cell metabolic reprogramming may underlie intrinsic tumor resistance. To characterize cancer cell metabolic response to SFB, we measured oxygen consumption, generation of reactive oxygen species (ROS) and ATP content in rat LCSC (Liver Cancer Stem Cells) -2 cells exposed to the drug. Genome wide analysis of gene expression was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 40 publications
7
60
0
1
Order By: Relevance
“…This finding indicates that sorafenib treatment suppresses mitochondrial energy conservation. Sorafenib has been previously reported to inhibit mitochondrial Complex I activity (61, 62). Importantly, mitochondrial depolarization by sorafenib treatment in the absence of ascorbate did not elicit the calcium increase and cell permeabilization, indicating that ascorbate is required for the dramatic rise in [Ca 2+ cyto ] and the effect of sorafenib treatment and the consequent mitochondrial depolarization is to sensitize the cells to the specific actions of ascorbate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicates that sorafenib treatment suppresses mitochondrial energy conservation. Sorafenib has been previously reported to inhibit mitochondrial Complex I activity (61, 62). Importantly, mitochondrial depolarization by sorafenib treatment in the absence of ascorbate did not elicit the calcium increase and cell permeabilization, indicating that ascorbate is required for the dramatic rise in [Ca 2+ cyto ] and the effect of sorafenib treatment and the consequent mitochondrial depolarization is to sensitize the cells to the specific actions of ascorbate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK can initiate autophagy through inactivation of mTORC1 or by phosphorylation of ULK1 [70, 71]. It is possible that sorafenib activates AMPK by inducing cellular ATP reduction and a corresponding increase in the AMP/ATP ratio [72, 73]. Curiously, there are differences in sorafenib-dependent modulation of AMPK in HCC cell lines, where AMPK and consequently autophagy were activated in Huh7, but not in Hep3B cells.…”
Section: Autophagy and Cancermentioning
confidence: 99%
“…Therefore, different autophagy responsiveness to sorafenib might be linked to generation of sorafenib resistance. Nevertheless, the AMPK pathway may be not involved in sorafenib-induced autophagy, since LC3-II was still upregulated significantly when AMPK was inhibited in HCC cells cultured with sorafenib [73, 74]. …”
Section: Autophagy and Cancermentioning
confidence: 99%
“…One study demonstrated that exposure of rat hepatocolangiocarcinoma cells to sorafenib induces increased rates of glycolysis 10 . Another study demonstrated that increased glycolytic utilization has a strong correlation with sorafenib resistance across several HCC cell lines 9 .…”
Section: Resultsmentioning
confidence: 99%
“…A handful of studies have demonstrated that a variety of mechanisms are involved in maintaining sorafenib resistance, which include CD44 overexpression 1 , activation of PI3K/AKT signaling 7 and increased MAPK14 activity 8 . Another group of studies has linked sorafenib sensitivity to cellular metabolism and glycolysis 9,10 . These studies are interesting because sorafenib therapy has been shown to inhibit oxidative phosphorylation and enhance glycolysis in a subset of HCC cell lines 2 .…”
Section: Introductionmentioning
confidence: 99%